Analysis of Vitamin D Levels on Bronchiectasis Severity - Yacob Arawamin Batkunde; Muhammad Ilyas; Irawaty Djaharuddin; Nur Ahmad Tabri; Harun Iskandar; Arif Santoso (Indonesian Society of Respirology (ISR), 2021)
Background: Bronchiectasis is a chronic disease caused by repeated infection and inflammation of the bronchial walls. Vitamin D plays a role secretion of antimicrobial peptide and inhibits release of pro-inflammatory cytokines in the lungs. Vitamin D deficiency is associated with exacerbations, severity and decreased lung function in bronchiectasis. Several studies have found an association between vitamin D levels and bronchiectasis severity. Methods: This study used cross-sectional study design with consecutive sampling method on bronchiectasis patients who enrolled outpatient and inpatient at Wahidin Sudirohusodo hospital in February - May 2020. All research procedures obtained the approval of the Health Research Ethics Commission, Medicine faculty, Hasanuddin University Makassar. Bronchiectasis severity was assessed based on the FACED score (FEV1, Aged, chronic Colonization by Pseudomonas aeuroginosa, radiological Extension of the disease, Dyspnea). Levels of vitamin D serum 25 (OH) D were checked using the ELISA method. Results: The study subjects were 44 patients, consisting of 61.4% male and 38.6% female. Most of the bronchiectasis patients in this study were mild (77.3%) based on the FACED score, 15.9% moderate and 6.8% severe. As many as 77.3% of patients had vitamin D deficiency and insufficiency as much as 9.1%. All patients with moderate-severe FACED scores had vitamin D deficiency. The correlation between vitamin D levels and FACED scores showed a positive significant with p-value 0.04. Conclusion: Low vitamin D levels are a risk factor for aggravating bronchiectasis severity and have a positive significant correlation between the two.